Analisis Potensi Ekowisata dan Kesiapan Masyarakat Desa Rendu Tutubadha dalam Pengembangan Ekowisata - Adriano Filemon Aja; I Nyoman Sukma Arida (JURNAL DESTINASI PARIWISATA, 2020)
Tourism trend and tourist motivation changes dynamically since the first time development of tourism. Mass tourism is one of tourism trend which grow Praccessibility, etc) and tour with a big group. Ecotourism appears in the early of 1990, ecotourism can be defined as a responsibility journey to a natural place. The aim is to make empowerement in the local society, conservancy, and the preservation of local society’s culture. Ecotourism grows fastly because this trend is different from conventional tourism which dominates. Rendu Tutubadha village locates in Aesesa District, Nagekeo Regency, East Nusa Tenggara Province has a big potential of ecotourism. Ecotourism potentials in this village consists of natural hot spring of Ae Petu Meze, Lambo Mountain, traditional village and etu ritual. Develop these ecotourism potentials needs readiness of Rendu Tutubadha’s society so the development will hold by the ecotourism principals and give positive effect to the society in eceonomis and other aspect. This research using primary and secondary data, quantitative and qualitative data is also used in this research. Data collecting method is interview, literature study, and observation. Qualitative descriptive used to presents the research result. This research finds some ecotourism potenstials in Rendu Tutubadha village. The ecotourism potential is nature and culture potential. The nature potential is like natural hot spring of Ae Petu Meze and Lambo Mountain, besides of that there are two culture potentials like traditional village of Rendu Tutubadha and Etu ritual. This research also finds that Rendu Tutubadha’s society readiness is enough to develop ecotourism, it can be seen in the society’s traditional life, although there are some aspects of ecotourism needs to fixed Keyword: ecotourism potential, ecotourism, society readiness